2022
DOI: 10.1002/anie.202114182
|View full text |Cite
|
Sign up to set email alerts
|

Cutting COF‐like C4N to Give Colloidal Quantum Dots: Towards Optical Encryption and Bidirectional Sulfur Chemistry via Functional Group and Edge Effects

Abstract: Herein, we report the first synthesis of colloidal C4N quantum dots (QDs) and their functional composites and explore their optical activities and edge‐selective polysulfide adsorption‐catalysis. As‐obtained C4NQDs are rich in carbonyl groups and edges, allowing good solution processability and facile assembly with other moieties for creating functionalities. While C4NQDs show normal fluorescence (FL), the QD/poly(vinyl alcohol) (PVA) composites give FL/room‐temperature‐phosphorescence (RTP) dual‐mode emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…1a From HR-TEM testing (Fig. 1d), two different widths of lattice stripes, 0.330 nm and 0.325 nm, can be observed, 18,19 which belong to C 4 N quantum dots and the (002) crystal plane of g-C 3 N 4 nanosheets, respectively. 25,26 In addition, according to the quantum dot size statistics of the AFM image for C 4 NQDs (Fig.…”
Section: Characterization Of Morphology and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…1a From HR-TEM testing (Fig. 1d), two different widths of lattice stripes, 0.330 nm and 0.325 nm, can be observed, 18,19 which belong to C 4 N quantum dots and the (002) crystal plane of g-C 3 N 4 nanosheets, respectively. 25,26 In addition, according to the quantum dot size statistics of the AFM image for C 4 NQDs (Fig.…”
Section: Characterization Of Morphology and Structurementioning
confidence: 99%
“…Previous reports have shown that the C 4 N polymer synthesized by adjusting the N/C stoichiometry could effectively narrow the band gap and promote charge separation, which was a new low band gap carbon nitride polymer. [18][19][20][21] More importantly, C 4 N and g-C 3 N 4 are also composed of C and N, which is more conducive to close integration. [22][23][24] Therefore, the combination of C 4 N dots and g-C 3 N 4 maybe a promising strategy for improving the photoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al reported a covalent organic framework (COF)-like C x N y material, C 4 N, with a C/N ratio of 4:1 connected with pyrazine, and subsequently prepared ultra-small colloidal C 4 N quantum dots (C 4 NQDs) with the average size of 2.2 nm (Fig. 10 a) [ 112 ]. Pyrazine N atoms and carbonyl groups at the edge of C 4 NQDs show preferential adsorption capability to LiPSs with significantly higher binding energy compared with that of the N sites in the C 4 NQDs plane (Fig.…”
Section: Other C X N Y ...mentioning
confidence: 99%
“…10 a Schematic illustration of the structure of C 4 N. b Adsorption energies for Li 2 S, Li 2 S 2 , Li 2 S 4 , Li 2 S 6 , and Li 2 S 8 on various sites of C 4 N. c Potentiostatic discharge curves and d potentiostatic charge curves of Li 2 S precipitation on the CP, C 4 NNSs/CP and C 4 NQDs/CP. e Cycling performance of cells with CNT modified separator and C 4 NQDs@CNT modified separator at 1.0C [ 112 ]. Copyright 2021, Wiley–VCH …”
Section: Other C X N Y ...mentioning
confidence: 99%
“…14−16 However, the reported COFs usually exist in the form of insoluble polycrystalline powders, which hinder their processing and shaping, thereby limiting their practical applications to some extent. Notably, reducing the size of COFs is an effective approach to enhancing their solubility or dispersibility, and the common reported methods include solvent-assisted ultrasound treatment 17 and ball milling, 18 etc. However, due to the high bond energy of covalent bonds within the COF structure, it is challenging to achieve bond breaking at the atomic level through simple ultrasonic treatment or ball milling, leading to limited size reduction and heterogeneous size distribution.…”
mentioning
confidence: 99%